FULFILLMENT OF THE STANDARD COMPONENTS OF HAJJ AND UMRAH SERVICES AT THE OFFICE OF THE MINISTRY OF RELIGION OF JENEPONTO REGENCY - Fajar, Muh Taufik; Nur, Andi Cudai; Yamin, Muh Nur (Universitas Negeri Makassar, 2025)
This study aims to determine the Quality of Hajj and Umrah Services at the Office of the Ministry of Religion of Jeneponto Regency. This research includes descriptive qualitative research with data collection techniques through observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and conclusion drawn. The results of the study show that the quality of the Fulfillment of the Hajj and Umrah Service Standard Components at the Office of the Ministry of Religion of Jeneponto Regency has not met the quality of service standards in the dimension of service quality stated by parasuraman et al. in Tjiptono (2000; 70) namely: 1) Direct Evidence, 2) Reliability, 3) Responsiveness, 4) Assurance, and 5) Emphaty. Of these five dimensions, they have not been able to provide quality services to the community. There are still several things that are the dimensions of Direct Evidence and Responsiveness. Further improvements are still needed which are important for the office of the Ministry of Religion of Jeneponto Regency to optimize Hajj and Umrah services and realize quality services